Métodos geofísicos aplicados à arqueologia no Estado do Pará - ALVES, José Jerônimo de Alencar (Universidade Federal do Pará, 2014)
This study is the first attempt to apply geophysical methods in research into archeological sites in Brazil. These methods were used with the objective of detecting archaeological remains in the sub-soil in two archaeological sites in the State of Pará: site PA-SA-4, from the Areão archaeological phase, and "Ilha dos Bichos" site from the Marajoara phase. In PA-SA-4, the magnetic method was employed, while at "Ilha dos Bichos" both electro-resistive and magnetic methods were used. The electro-resistive method made possible the determination of the occupied layers, since these behave like geoelectrical beds, different from those of the geological formations of the area. It also permitted the detection of compact layers of clay, planars and horizontals, of archaeological origin, located on the east side of the "Ilha dos Bichos". The magnetic method led to the detection of ancient firing places, thanks to the thermo-remnant acquired by the clay in the process of heating/cooling, and thus permitted the discovery of ancient kilns, as well as a burial urn under a thick bed of burnt clay.